Using innovative equipment FrymaKoruma MaxxD in the production of mayonnaise - Паска, Марія Зіновіївна; Жук, Олександр Іванович (Eastern-European Journal of Enterprise Technologies, 2015)
Using the equipment of the FrymaKoruma MaxxD vacuum processing unit for liquid and pasty products is a topical issue today. The advantages of such equipment are highly efficient production with low operating costs and high performance, preset parameters ensure consistent quality of the product, the final product is stable, homogeneous, and air-free, versatility: the machine is able to manufacture a great variety of products of different volumes and with different technologies. The advantages of the Silverson mixing technology lie in the fact that one unit can perform tasks, for implementing which in the past several different pieces of production equipment could be used. Due to excellent operational adaptability, each unit can perform a wide range of functions: blending, dispersion, emulsification and homogenization, particle size reduction and dissolution.